PENAMBATAN MOLEKULER SENYAWA XANTON PADA KULIT BUAH MANGGIS (Garcinia Mangostana L.) DENGAN ENZIM COX-2 Sebagai Kandidat Antikanker Payudara. - Herson Cahaya Himawan; Lilik Sulastri; Verari Vernando (Jurnal Farmamedika (Pharmamedika Journal), 2018)
Breast cancer is one of the most common types of cancer suffered by women around the world. Breast cancer is known that has relationship with chronic inflammation that is controlled by cyclooxygenase-2 (COX-2). Pericarp of mangosteen (Garcinia mangostana L.) contains a class compound of xanthone. The compound has potential as an inhibitor of the COX-2enzyme.The purpose of this research is to know the most active compound of xanthone compounds. Potential of xanthone compounds tested the toxicityby using Toxtree, the analysis of toxicity is focused on the carcinogenycity and mutagenicity.The result of toxicity test of ligand compound with Toxtree software found that the compound of 1-Isomangostin hydrate, 3-Isomangostin hydrate, Euxanthon, BR-xanthone A,Garcimangosone B and Garcimangosone D predicted safe for use as medicine. Then the compound itself analyzed based on the criteria of Lipinski's Rule of Five to predict the drug absorption in the human body. The analysis showed,five compounds fulfilled the criteria of Lipinski except Garcimangosone D. Further analysis was molecular docking using Autodock VinaA had a binding energy (ΔG) the best that was -10.1 kcal / mol if it compared to other test compounds, approaching the binding energy (ΔG) comparative compound of celecoxib -12.4 kcal / mol.